PENGARUH PENDEKATAN OPEN ENDED TERHADAP HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS VIII SMPN 2 TANGERANG SELATAN - Alvina Aulia; Esti Ambar Nugraheni (SIGMA, 2022)
This study aims to analyze the effect of the open-ended approach on the mathematics learning outcomes of students of class VIII SMPN 2 South Tangerang. The types of research used are experimental methods, quantitative approach, and true experimental design techniques using the randomized pretest-posttest control design. This research was conducted at SMPN 2 South Tangerang from October 18 to November 12 in class VIII-6 as many as 30 students as the experimental class and class VIII-5 as many as 30 students as the control class. The data collection technique used is esai tests with five questions. Meanwhile, the data analysis used descriptive statistical tests, normality tests, homogeneity tests, and hypothesis testing using paired samples t-test. The results showed there increase in mathematics learning outcomes of students of class VIII SMPN 2 South Tangerang for the experimental group by 49,90% and the control group by 25,30%. Based on the results of data analysis, it can conclude that there is an effect of the open-ended approach on the mathematics learning outcomes of students of class SMPN 2 South Tangerang.